The Impact of Profit Expectations and Accounting Information Systems Understanding on Entrepreneurial Interest - Endrawati, Endrawati; Santi, Elfitri; Gustati, Gustati; Oliyan, Fitra; Rahmadani, Suci (International Ecsis Association, 2023)
The purpose of this study was to see the effect of expected earnings and understanding of accounting information systems on students' interest in entrepreneurship. This research uses quantitative methods through a survey approach and multiple linear regression. Purposive sampling is the sampling technique used. The sample in this study consisted of 203 students majoring in accounting at the Politeknik Negeri Padang. Students majoring in accounting at Politeknik Negeri Padang had a significantly positive relationship between the profit expectation variable and their interest in entrepreneurship. Students' interest in entrepreneurial will be piqued to a greater extent if there is a greater expectation of student-generated profit. Understanding accounting information systems, however, has little impact on a person's desire in starting a business. This shows that not all students who have a solid understanding of accounting information systems are interested in entrepreneurial spirit, and that only a small number of persons can easily understand and apply accounting information systems to entrepreneurial. Simultaneously, profit expectations and understanding of accounting information systems affect interest in entrepreneurship. This shows that profit expectations and an understanding of accounting information systems together can increase students' interest in entrepreneurship.